Diurnal and nocturnal scavenger communities differ at two shallow-water depths in an Irish marine lough. (5th November 2021) - Davenport, John; Jessopp, Mark; Harman, Luke; Micaroni, Valerio; McAllen, Rob
Abstract: We report on still/video photographic studies in 2018/9 of diurnal and nocturnal benthic scavenging on carrion in shallow water (2 m and 12 m depths) within Lough Hyne (a biodiverse Irish sea lough) using natural light during replicated 6 h daytime deployments and dim red light (630 nm) during 6 h deployments at night. In 2018 at 2 m depth in the North Basin, bait was present throughout day-time deployments, showing little evidence of scavenging; scavenger species' richness and abundance were low. At night, baits disappeared or were skeletonised; they were scavenged by a significantly more abundant and species-rich scavenger guild. At 12 m depth in the same basin, baits were removed or skeletonised during day and night. This confirmed our hypothesis that scavengers avoid well-lit very shallow water during the day, probably to avoid predation. Multivariate analysis of 2018/19 still photo data (12 m depth) revealed pronounced and statistically significant separate clustering of day, night and basin abundance/species data, although overall species' richness values did not differ significantly. These analyses together reflected differences in species' compositions associated with contrasting sediments, flow regimes and night/day. Nephrop s norvegicus, Pagurus bernhardus and Crangon crangon were only found in the low flow rate North Basin; Homarus gammarus, Trigla sp., Callionymus lyra, Agonus, Tritia reticulata and Marthasterias glacialis were only found in the high flow rate South Basin. Most scavenger species foraged in both day and night (though in different proportions). However, prawns ( Palaemon serratus ) only appeared at night. Small mobile scavenging fish, small crabs and prawns arrived at baits within seconds to minutes, as did locally-abundant slow movers (e.g. anemones ( Anthopleura ballii ), whelks ( T. reticulata )). These times are shorter than recorded in earlier studies in deeper water. Larger crustaceans (e.g. Cancer pagurus, H. gammarus ) took tens of minutes to hours before arrival; similar times have previously been recorded in deeper water. Large crustacean scavengers ( C. pagurus, Maja squinado, H. gammarus ) took substantial quantities of bait during long feeding bouts, but catsharks ( Scyliorhinus canicula ) often took similar quantities in a few seconds. All of the dominant scavenger species are broad-spectrum omnivores; only one obligate scavenger species ( Tritia reticulata ) was present (only in South Basin) and consumed negligible quantities of bait. Highlights: Dim red illumination permitted effective study of nocturnal marine scavenging. Night-time scavenging was much more intense and species-rich than in day-time at 2 m depth. Scavenger communities varied geographically and temporally. Prawns Palaemon serratus only scavenged at night but were effective bait macerators. Crustacea spent long periods feeding on bait; fish, including catsharks fed for seconds at a time.